Advancing Electrocatalytic CO2 Conversion: From Catalyst Design to Practical Applications - Pan Lechen (MATEC Web of Conferences, 2025)
Electrocatalytic CO2 conversion has emerged as a promising strategy for mitigating climate change by transforming CO2 into valuable chemicals and fuels. This paper provides a comprehensive analysis of recent advancements in electrocatalyst design, reaction mechanisms, and system integration to enhance CO2 reduction efficiency. Traditional approaches, such as thermochemical and photocatalytic methods, encounter significant challenges, including high energy consumption and low selectivity. In contrast, electrocatalysis offers tunable reaction pathways and compatibility with renewable energy sources. Key topics discussed include the classification of catalyst materials, including metal-based, carbon-based, and molecular catalysts, with their performance metrics (such as Faradaic efficiency and overpotential), and the scalability challenges they face. Case studies highlight pilot-scale applications and industrial partnerships, while addressing degradation mechanisms and strategies for cost reduction. The review concludes with a look at future directions, emphasizing the need for earth-abundant catalysts, advanced characterization techniques, and hybrid systems that integrate carbon capture. This work underscores the potential of electrocatalysis to enable sustainable CO2 utilization, contributing to global decarbonization goals.